Density functional theory study of the reactivity and electronic structure of the transesterification of triacetin in biodiesel production via a sulfated zirconia heterogeneous catalysis. Issue 13 (27th February 2016) - Muñiz, Jesús; Castillo, Roger; Robles, José B.; Sansores, Enrique
Abstract : This DFT study examined the interaction of a sulfated zirconia (SZ) slab model system (heterogeneous catalyst) and triacetin (a precursor in biodiesel production) using explicit methanol solvent molecules. Full geometry optimizations of the systems were performed at the B3LYP level of theory. Gibbs free energies provide insight into the spontaneity of the reactions along a three‐step reaction mechanism for the transesterification of triacetin. Charge decomposition analysis revealed electronic charge transfer between the metallic oxide and the organic moieties involved in the reaction mechanism. Fukui indices indicate the likely locations on the SZ surface where catalysis may occur. The quadratic synchronous transit scheme was used to locate transition structures for each step of the transesterification process. The results are in agreement with the strongly acidic catalytic character of zirconium observed experimentally in the production of biodiesel. © 2016 Wiley Periodicals, Inc. Abstract : Biodiesel is seen as an environmentally sustainable alternative to the use of fossil fuels. The reaction mechanism and charge transfer of triacetin, a precursor in biodiesel production, on sulfated zirconia as a heterogeneous catalyst can be analyzed using computational chemistry techniques. The study provides an insight on the catalytic properties of sulfated zirconia and its role on the transesterification of triacetin.